AMBULATORY BLOOD PRESSURE TRAJECTORIES AND BLOOD PRESSURE VARIABILITY IN KIDNEY TRANSPLANT RECIPIENTS: A COMPARATIVE STUDY AGAINST CHRONIC KIDNEY DISEASE PATIENTS. (June 2022) - Korogiannou, Maria; Theodorakopoulou, Marieta; Sarafidis, Pantelis; Alexandrou, Maria Eleni; Pella, Eva; Xagas, Efstathios; Argyris, Antonis; Protogerou, Athanase; Papagianni, Aikaterini; Boletis, Ioannis N.; Marinaki, Smaragdi
Abstract : Objective: Hypertension is a major cardiovascular risk factor in both kidney transplant recipients (KTRs) and patients with chronic kidney disease (CKD). Ambulatory blood pressure monitoring (ABPM) is considered the gold-standard method for hypertension management in these subjects. This is the first study evaluating in comparison the full ambulatory BP profile and short-term BP variability (BPV) in KTRs versus CKD patients without kidney replacement therapy. Design and method: 93 KTRs were matched with 93 CKD patients for age, sex and eGFR. All participants underwent 24-h ABPM; mean ambulatory BP levels, BP trajectories and BPV indices [standard deviation (SD), weighted-SD and average real variability] were compared between the two groups. Results: There were no significant between-group differences in 24-hour SBP/DBP (KTRs:126.9 ± 13.1/79.1 ± 7.9 vs CKD:128.1 ± 11.2/77.9 ± 8.1mmHg, p = 0.522/0.293), daytime SBP/DBP and nighttime SBP; nighttime DBP was slightly higher in KTRs (KTRs:76.5 ± 8.8 vs CKD:73.8 ± 8.8mmHg, p = 0.040). For both ambulatory SBP/DBP, repeated-measurements-ANOVA showed a significant effect of time (SBP: F = [19, 3002] = 11.735, p < 0.001, partial 2 = 0.069) but not of KTR/CKD status(SBP: F = [1, 158] = 0.668, p = 0.415, partial 2 = 0.004). Ambulatory systolic/diastolic BPV indices were not different between KTRs and CKD patients, except for 24-hour DBP-SD that was slightly higher in the latter (KTRs:10.2 ± 2.2 vs CKD:10.9 ± 2.6mmHg, p = 0.041). No differences were noted in dipping pattern between the two groups. Conclusions: Mean ambulatory BP levels, BP trajectories and short-term BPV indices are not significantly different between KTRs and CKD patients, suggesting that KTRs have a similar ambulatory BP profile compared to CKD patients without kidney replacement therapy.